Pendidikan Islam dan Lapangan Kerja - Mifedwil Jandra (LP2M UIN Sunan Kalijaga, 2018)
Today the Islamic education is faced with the challenge of modern human life that is filled with a variety of issues are quite complex, among other things how the Islamic education able to prepare human quality, high morals in the face of societal changes so quickly, so that the products of Islamic education is to serve the needs of the hereafter but should be able to compete in a competitive and proactive in the world of modern society. In life and work, it teaches the importance of future-oriented. This grows with consequent attitude in the form of behavior that always lead to efficient ways of working (energy saving). This attitude is the basis in an effort to make the man who is always oriented to the productive values. Casual work, without a plan, lazy, wasteful of energy, time and costs is contrary to Islamic values. Islam teaches that every second of the time should be filled with three things; increase in faith, pious charity and social communication.